Construction and characterization of cultural landscape genomic maps of traditional miao communities in Leigong Mountain - Han Gu; Hongyu Chen; Yiting Luo; Ke Xu (Journal of Asian Architecture and Building Engineering)
In the era of farming civilization, traditional villages serve as carriers for value retention. In the context of urban – rural integration, exploring the means for protecting the traditional Miao villages in Leigong Mountain, Qiandongnan, holds great significance. This region contains abundant cultural landscape resources. Revitalizing the environment for the survival of their cultural landscapes is also a crucial aspect. In the present study, 20 Miao traditional villages in Leigong Mountain, Qiandongnan, were selected as subjects. ArcGIS10.8 was used as the technical platform to construct five types of cultural landscape genome mapping systems, namely cultural landscape factor information mapping, spatial sequence mapping, public space pattern mapping, arrangement pattern mapping, and spatial pattern mapping. This was achieved by analyzing individual traditional villages, multiple traditional villages, and a specific study area. Based on this analysis, this study summarizes the four basic features of cultural landscape architecture, namely culture, environment, and layout of the traditional Miao villages in Leigongshan. This study clarifies the spatial distribution pattern of the cultural landscape genome of traditional gMiao villages in Leigong Mountain by constructing an atlas and identifying the relationship between the mutual influences of various elements during the development and evolution of the villages. Based on the findings, this study provides a reference basis for protecting the cultural landscape of traditional villages and promote further research at the regional level.